Efektivitas Intervensi Brain Gym Exercise Terhadap Peningkatan Kognitif Tahun 2021 (Studi Kuasi Eksperimen : Pada Lansia Di Panti Sosial Tresna Werdha Budi Mulya I) - Ratu Karel Lina; Sri Yani; R Trioclarise (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Background : The existence of the elderly population is scattered in both urban and rural areas. One of the problems that are often experienced by the elderly is cognitive impairment. Cognitive changes that occur in the elderly are shown through intellectual decline, especially on tasks that require speed and short-term memory. One of the exercises that can be given to the elderly in cognitive improvement is brain gym exercise which aims to increase self-confidence, stimulate the right and left brain, relax the brain. Objective: To determine the effect of brain gym exercise on cognitive in the elderly. Research Methods : Quasi experimental with “Two-group pretest-posttest design”. The research was carried out at the Tresna Werdha Budi Mulya I Social Institution, East Jakarta, from January to November 2021. This study required two groups with a sample size of 15 people per group. The stages of data collection were preparation (informed consent), pre-intervention (Mini Cognitive Test), intervention (brain gym exercise and education) in the treatment group, and education in the control group. given 3 times a week for 15 minutes for 3 weeks, and the post-intervention stage. Result: There was a significant difference in cognitive average between before and after the Brain Gym Exercise intervention in the elderly (p = 0.0001), there was no significant difference in cognitive average between before and after the physiotherapy education intervention in the control group (p = 0.334), and there was a difference in the mean cognitive score between the case group and the control group after the intervention (p = 0.0001). Conclusion: Brain Gym Exercise intervention is effective in improving Cognitive in the Elderly.